PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA ORGANISASI KECAMATAN DI KOTA SEMARANG - Khansa, Haifa Kamilla; Raharjo, Teguh Hardi (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyse how organisational culture and work motivation influence the performance of sub-district government offices in Semarang City. Amid the increasing demands for public service accountability and performance improvement, it is essential to understand how internal organisational factors affect government performance.Methods: The study adopts a quantitative explanatory research design with an associative approach. Data were collected through questionnaires distributed to 159 respondents, selected using proportionate stratified random sampling from a population of 528 employees across 16 sub-district offices. The data were analysed using multiple linear regression and classical assumption tests.Results: The results demonstrate that organisational culture and work motivation positively and significantly impact organisational performance, individually and simultaneously. Organisational culture has a positive impact on employees’ behaviour and work environment, while work motivation drives productivity and engagement. Together, these factors contribute significantly to enhancing the performance of sub-district government organisations.Conclusion and suggestion: In conclusion, strengthening a performance-oriented organisational culture and implementing motivation strategies—such as fair rewards, career development, and participatory leadership—are key to improving public service quality. Local governments should continuously build internal capacity by aligning values, leadership, and motivation mechanisms to ensure sustainable organisational performance. Keywords: Organizational Culture, Work Motivation, Organizational Performance, Sub-District Government